2010
DOI: 10.3390/medicina46010004
|View full text |Cite
|
Sign up to set email alerts
|

Significance of operative parameters on outcomes after transurethral resection of the prostate

Abstract: as the strongest independent predictor of ineffective outcome. Logistic regression analysis revealed two important parameters of unfavorable outcomes: residual prostatic weight ratio (cutoff value, 0.71; P<0.001; OR, 62.16) and residual prostate weight (cutoff value, 26.6 mL; P=0.013; OR, 9.98). When the values of both these parameters were lower than their cutoff values, the probability of an ineffective outcome was reduced to 3%; however, when they were higher, the probability of an unfavorable outcome was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…16 However, it has been frequently reported that patients with BPH suffered from LUTS, stress, anxiety, depression, and incapacity to complete basic tasks due to the psychological impacts. [17][18][19][20] Previous studies on BPH patients who undergoing TURP only emphasized the examination of postoperative comorbidities or the technical success of the operation, whereas seldom paid attention to the correlations between TURP treatments for BPH and the adverse psychological effects.…”
Section: Discussionmentioning
confidence: 99%
“…16 However, it has been frequently reported that patients with BPH suffered from LUTS, stress, anxiety, depression, and incapacity to complete basic tasks due to the psychological impacts. [17][18][19][20] Previous studies on BPH patients who undergoing TURP only emphasized the examination of postoperative comorbidities or the technical success of the operation, whereas seldom paid attention to the correlations between TURP treatments for BPH and the adverse psychological effects.…”
Section: Discussionmentioning
confidence: 99%
“…The biggest challenge in the present study was to estimate model inputs, due to lack of local data in published literature. Clinical data were based on the pivotal trial (the ComBAT study), incidence, prevalence of BPH and LUTS [ 29 ] data were extracted from European sources [ 22 , 23 ], and were subsequently confirmed by the expert panel. Our analysis was performed with inclusion of all patients, regardless of pre-treatment prostate volume (326,000 men estimation).…”
Section: Discussionmentioning
confidence: 99%
“…Transurethral resection of the prostate (TURP) is an effective treatment modality for lower urinary tract symptoms (LUTS) secondary to a benign obstruction of the prostate (BOP) [ 1 ]. However, in some patients, the improvement of symptoms after TURP is insufficient [ 2 , 3 ]. Therefore, studies have been conducted to detect parameters that can predict outcomes after the intervention.…”
Section: Introductionmentioning
confidence: 99%